Changes in running biomechanics during the 2017 IAAF world championships men's 1500 m final - Hanley, B.; Bissas, A.; Merlino, S.; Burns, G. T. (Scandinavian Journal of Medicine & Science in Sports, 2023)
The aim of this study was to analyze key kinematic, spatiotemporal, and global mechanical characteristics in world-class middle-distance racing. Eight men were recorded halfway along the home straight on the second, third, and final laps in the 2017 IAAF World Championship 1500 m final. Video data (150 Hz) from three high-definition camcorders were digitized to calculate relevant variables, subsequently analyzed in relation to running speed and finishing position. Better-placed finishers had greater hip extension at initial contact and through late stance, greater knee excursion throughout stance, and longer overstriding distances. Step length did not change with faster speeds as runners relied on increasing step frequency, but the highest-finishing athletes had longer contact phases and greater fluctuations in speed through the step cycle, which were related to higher normalized peak horizontal forces. The best athletes also had lower leg stiffnesses and vertical stiffnesses. The extended contact phase and greater compression could allow for more sustained force production, enabling better acceleration and maintenance of sprinting speed, indicating a trade-off between aerobic energetic efficiency and anaerobic power capacity. Coaches should note that these factors, as well as the best athletes' greater overstriding distances, show that elite 1500 m runners might prioritize a technique that favors running speed over economy.